0
$\begingroup$

I am familiar with the next reasoning for multinomial probability function: $P(X_1 = x_1 , X_2 = x_2,...,X_k = x_k)$ when $x_1 +x_2+...+x_k =n$ and $p_1,p_2,...,p_k$ are the probabilities to choose an element from kind $X_i$. So the probability for a specific sequence of $n$ elements $(e_1,e_2,...,e_n)$ such that the number of elements from type $X_i$ is $x_i$ for each $1\le i \le k$ is $p_1^{x_1}p_2^{x_2}...p_k^{x_k}$ and the number of sequences which fulfill those condition is ${n\choose x_1}{n-x_1\choose x_2}...{n-(x_1+x_2+...+x_{k-1})\choose x_k} = \frac{n!}{x_1!x_2!...x_k!}$ so the probability $P(X_1=x_1,...,X_k=x_k) = \frac{n!}{x_1!x_2!...x_k!} \cdot p_1^{x_1}p_2^{x_2}...p_k^{x_k} $.

However I fail to derive this probability using conditional probability, what I tried to do for the tri-nomial case, i.e $P(X_1 = x_1 , X_2 = x_2 , X_3 = x_3)$ given $x_1+x_2+x_3 = n$ and the respective probabilities $p_1,p_2,p_3$. So, $P(X_1=x_1 , X_2 = x_2, X_3 = x_3)=P(X_1=x_1 ,X_2 =x_2)$ since in case $P(X_1 = x_1 , X_2 =x_2)$ and total number of elements is $n$ then $X_3 = x_3$. Using condition probability:

$P(X_1 = x_1, X_2 = x_2) = P(X_1 = x_1 | X_2 = x_2) \cdot P(X_2 = x_2)$, for $P(X_2 = x_2)$ we get ${n\choose x_2}p_2^{x_2}(1-p_2)^{n-x_2}$ and $P(X_1=x_2 | X_2 = x_2) = {n-x_2\choose x_1}p_1^{x_1}(1-(p_2-p_1))^{n-x_2-x_1} = {n-x_2\choose x_1}p_1^{x_1}(p_3)^{x_3}$.

So multiplying gives: ${n\choose x_2}p_2^{x_2}(1-p_2)^{n-x_2} \cdot {n-x_2\choose x_1}p_1^{x_1}p_3^{x_3} = \frac{n!}{x_1 ! x_2 ! x_3 !}p_1^{x_1} p_2^{x_2} p_3 ^{x_3}(1-p_2)^{n-x_2}$.

Well it is definitely wrong, but I don't see what am I doing wrong, I think I missed calculated the conditional probailty $P(X_1 = x_1 | X_2 = x_2)$ yet I don't see what is wrong.

$\endgroup$
1
$\begingroup$

Among the $n-x_2$ entries which are not $X_2$-kind, the probability that a particular one is $X_1$-kind is ${p_1 \over p_1 + p_3} = {p_1 \over 1 - p_2}$. You are conditioning on that entry not being $X_2$-kind. So

$$P(X_1 = x_1 \mid X_2 = x_2) = {n-x_2 \choose x_1} ({p_1 \over 1-p_2})^{x_1} ({p_3 \over 1-p_2})^{x_3} = ({1\over 1-p_2})^{n-x_2} {n-x_2 \choose x_1} p_1^{x_1} p_3^{x_3}$$

and now when you multiply everything together you get consistent results.

Hint: next time try a very simple example. E.g. if you tried $p_1=p_2=p_3 =1/3$ and $n=2, x_2=1$, you could tell that $P(X_1=1, X_3=0 \mid X_2=1)$ should have been $1/2$ by symmetry, and therefore your original formula giving $1/3$ is wrong.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.